Coping with 'Dark Sides of the Sun' through Photoreceptor Signaling. (March 2018) - Demarsy, Emilie; Goldschmidt-Clermont, Michel; Ulm, Roman
Abstract : Plants grow in constantly changing environments, including highly variable light intensities. Sunlight provides the energy that drives photosynthesis and is thus of the utmost importance for plant growth and the generation of oxygen, which the majority of life on Earth depends on. However, exposure to either insufficient or excess levels of light can have detrimental effects and cause light stress. Whereas exposure to insufficient light limits photosynthetic activity, resulting in 'energy starvation', exposure to excess light can damage the photosynthetic apparatus. Furthermore, strong sunlight is associated with high levels of potentially damaging UV-B radiation. Different classes of photoreceptors play important roles in coping with the negative aspects of sunlight, for which specific mechanisms are emerging that are reviewed here. Highlights: Light is essential for plants, both as a source of energy for photosynthesis and as an environmental informational signal interpreted by specific photoreceptors. Many links exist between photoreceptor signaling and the optimization of photosynthesis. Sunlight can be an environmental stress for plants because, in excess, it can overwhelm the normal photosynthetic capacity and because it has an intrinsic, potentially damaging UV-B component. However, plants have evolved mechanisms, several of which are regulated by photoreceptor signaling, to protect themselves from the negative effects of excess sunlight. Photoreceptor-mediated optimization of photosynthesis and photoprotection is important and is therefore broadly conserved across 'green plants' (Viridiplantae); however, the specific mechanisms may differ among organisms.